Candidiasis in breast cancer: Tumor progression or not? - Somayeh Ashrafi; Abbas Ali Amini; Pegah Karimi; Maryam Bagherian; Mohammad Mahdi Adibzadeh Sereshgi; Fatemeh Asgarhalvaei; Khadijeh Ahmadi; Mohammad Hossein Yazdi; Hamidreza Jahantigh; Mehdi Mahdavi; Ramin Sarrami Forooshani (Iranian Journal of Basic Medical Sciences, 2024)
Candida albicans is an “opportunistic fungal agent” in cancer patients that can become colonized in both mucosal and deep tissues and cause severe infections. Most evidence has shown that C. albicans can enhance the progress of different cancers by several mechanisms such as generating virulence factors, participation in endogenous production of pro-inflammatory mediators, and stimulating a wide range of immune cells in the host. The main idea of this review is to describe a range of Candida-used mechanisms that are important in candidiasis-associated malignant processes and cancer development, particularly breast cancer. This review intends to provide a detailed discussion on different regulatory mechanisms of C. albicans that undoubtedly help to open new therapeutic horizons of cancer therapy in patients with fungal infection. The current therapeutic approach is not fully effective in immunocompromised and cancer patients, and further studies are required to find new products with effective antifungal properties and minimal side effects to increase the susceptibility of opportunistic fungal infections to conventional antifungal agents. So, in this situation, a special therapy should be considered to control the infection and simultaneously have the most therapeutic index on tumor patients.